Pembangunan Sistem Informasi Manajemen Laboratorium Terpadu Universitas ABC - Saputra, Dimas; Atrinawati, Lovinta Happy; Putera, M. Ihsan Alfani (STIKOM Tunas Bangsa Pematangsiantar, 2021)
The need for information technology at this time has become an obligation for every company or organization. One that applies the development of information technology is ABC University. ABC University is a university that was founded in 2012 and along with the development of educational infrastructure every year, in 2020 ABC University has just completed the construction of an integrated laboratory building that functions as a place for research, learning, and academic and non-academic activities. This Integrated Laboratory will be used by 17 study programs at ABC University, more than 3000 students as well as lecturers and the academic community. With the limited number of rooms and laboratory assets for a large number of laboratory users, a system that functions to facilitate the use of laboratories is needed, starting from scheduling laboratory use, borrowing laboratory space, and borrowing laboratory equipment, Therefore, an information system needs to be developed in order to meet the needs of the ABC University Integrated Laboratory, namely the ABC University Integrated Laboratory Management Information System (MIS). The method used in developing this Integrated Laboratory SIM is the Scrum method which includes sprint planning, daily scrum, sprint review, and sprint retrospective. Based on 5 iterations during the development process of the Integrated Laboratory MIS, the total backlog items obtained were 65 backlog items. The ABC University Integrated Laboratory MIS has also been hosted on ABC University's servers and can be accessed via the https://labterpadu.itk.ac.id link.